The impact of sexual harassment hashtags: #MeToo towards #MakeSchoolASaferPlace in Malaysia - Azlan Razif, Sarah Dalfina (2022)
Sexual harassment is a serious problem in society, it is an offensive behavior and a crime. One of the most known sexual harassment hashtags to date is the #MeToo movement. This movement has impacted the social media world by storm. It started out as a simple Tweet and it eventually turned into a viral phenomenon because of all the other survivors slowing telling their stories. The breakthrough moment for survivors of sexual harassment to fight for justice. More and more women began using the hashtag, and it eventually became a trending topic. This brought attention to the public as well as media outlets which led to a few famous predators being called out for their crimes.